An initial study in the development of smartphone addiction scale for student (SAS-S) - Habibi, A Maulani; Sanyata, Sigit (COUNS-EDU: The International Journal of Counseling and Education, 2018)
The purpose of this study was to develop a new scale, Smartphone addiction scale for Student (SAS-S) was developed to measure the level of smartphone addiction in high school students. A total of 32 item scales were developed through literature studies. Exploratory factor analysis (EFA) is used to examine the structure of factors formed in this scale. The results show the Smartphone addiction scale for Student (SAS-S) has 22 good items from 6 factor structures that are formed, including: (1) Self Control Disorder, (2) loss of time, (3) sleep disturbances, (4) can not be without smartphones, (5) changes in feelings and, (6) concerned smartphone. SAS-S is a good scale that can be used by any high school student. Another point also shows that the scale of smartphone addiction for high school students has a strong level of validity and reliability.